Novel Active Learning Experiences for Students to Identify Barriers to Independent Living for People with Disabilities. Issue 4 (July 2016) - McArthur, Polly; Burch, Lillian; Moore, Katherine; Hodges, Mary Sue
Abstract : Purpose: : This article describes interactive learning about independent living for people with disabilities and features the partnership of the College of Nursing and a Center for Independent Living (CIL). Design: : Using qualitative descriptive approach, students' written reflections were analyzed. Methods: : Through "Xtreme Challenge, " 82 undergraduate nursing students participated in aspects of independent living as well as identifying barriers. Findings: : Students were engaged and learned to consider the person before the disability. Moreover, students valued the activity leaders' openness, which facilitated understanding the point of view of a person with disability. Conclusions: : The value of partnership was evident as it allowed students to participate in active learning, which led to growth in the affective domain. Students became aware of potential education resources through the CIL. Clinical Relevance: : This article will guide educators in designing experiences that teach nursing care at the individual, family, and community level for people living with disabilities.